Discovery and statistics of Be stars - Jaschek, Carlos (1962)
In 1960, the authors have started at the La Plata Observatory a survey of bright B stars (m ≤ 6.5, δ< 0°, HD Spectral type 09-B5) for the discovery of emission in Hα. A two prism spectrograph attached to the 80 cm La Plata telescope was used, with a camera giving a dispersion of 180 A/mm. The slit was opened as much as possible in order to shorten the exposure times; as a consequence the region of good definition on the plates comprises only from 6000 to 6700 A.